(untitled) (Dhaka University Journal of Biological Sciences, 2012)
This study evaluated the haematological profile of air breathing Thai and indigenous male and female climbing perch (in Bangla, koi) Anabus testudineus to improve understanding the differences between two strains at blood parameters level. Haemoglobin (Hb), haematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), erythrocyte red blood cells (RBC) or erythrocytes, lymphocytes, monocytes, neutrophils and eosinophils were identified by mythic 18 automated haematology analyzer. Most haematological parameters indicated significant (p < 0.05) intra species sex variations. Higher Hb concentration, RBC counts and HCT percentages were found in Thai and indigenous males compared to their counterparts but higher MCH values, WBC counts and ESR levels were detected in both Thai and indigenous females than in the males. Similar concentration of Hb was detected in the same sex between fish. In contrast, higher level of ESR was observed in both female than did the males. Total counts of RBC observed in both Thai and indigenous male was significantly higher than in the females. MCV was found higher in indigenous male and female than in Thai one. However, no significant differences were observed in neutrophils, lymphocytes and eosinophils. Findings of this study showed sex variations in the haematological parameters between Thai and indigenous climbing perch. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9746 DUJBS 2012 21(1): 67-77